2016
DOI: 10.17706/ijbbb.2016.6.4.139-144
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Plain Medium Resistant of Chrysanthemum Planlet Produced of Gamma Ray Irradiation

Abstract: Genetic diversity can be improved using the gamma ray irradiation to obtain the resistant plants to the disease. The Changes occur can be analyzed at the beginning of plant growth using molecular analysis; RAPD technique (Random Amplified Polymorfism DNA). This study aims to determine the genetic diversity produced by gamma rays irradiated and given the poly ethilene glycol given in plantlets to increase chrysanthemum resistance to Medium plain. The study used four primers tested on four treatments that were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In terms of root length, the treatment using activated charcoal norit showed significantly longer roots than other kinds of activated charcoal because the activated charcoal in norit could reduce the light coming into the growing medium. Notably, pro-analysis activated charcoal and norit contained a higher percentage of activated charcoal, approximately 99 percent, while plant-derived activated charcoal contained 95-99 percent [1,8]. On the other hand, activated charcoal derived from coconut shells showed better overall performance than plant-derived activated charcoal, although it was still lower than norit.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In terms of root length, the treatment using activated charcoal norit showed significantly longer roots than other kinds of activated charcoal because the activated charcoal in norit could reduce the light coming into the growing medium. Notably, pro-analysis activated charcoal and norit contained a higher percentage of activated charcoal, approximately 99 percent, while plant-derived activated charcoal contained 95-99 percent [1,8]. On the other hand, activated charcoal derived from coconut shells showed better overall performance than plant-derived activated charcoal, although it was still lower than norit.…”
Section: Resultsmentioning
confidence: 94%
“…Sugar exists in large amounts in sweet fruits, stems, roots, tubers, and the sap of some higher plants, where saccharose is soluble in water. Saccharose functions in the thickening of cell walls, while auxin is a catalyst in the metabolism of carbohydrates and in regulating mitosis activity [1,18]. Wijayani and Muafi [11] conducted studies on Chrysanthemum plant tissue culture using ½ MS medium, and 40 g/l saccharose showed faster growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mutation was closely related to the dosage of gamma rays applied [11]. In another study conducted by Wijayani and Amiaji [9] that used colchicine, there was a change in the color into yellowish green, which is assumed to be caused by the application of too little concentration of colchicine. According to Chandler and Brugliera [12], colchicine will be effective in the concentration of 0.1 -0.8 percent, with soaking time of 24-96 hours.…”
Section: B Colour Quality Testmentioning
confidence: 99%